KAMPANYE KESADARAN MASYARAKAT MENGENAI PELESTARIAN CAGAR BUDAYA BERDASARKAN UNDANGUNDANG NOMOR 11 TAHUN 2010 - Yosua Adrian Pasaribu (Pusat Penelitian Arkeologi Nasional, 2018)
Abstract.Law Number 11 of 2010 Concerning Cultural Conservation commands people to register their object, building, structure, site, or area which have significant values for the history, science, education, religion, and/or culture to regency/municipal governments for feasibility study as cultural heritage. In order to implement the law, since 2013 the government has conducted socialization to 69% of local governments. However, the responds from regency/municipal governments in terms of organizing cultural heritage registration for public is relatively low. By the end of 2017, there have only been 13.5% of local governments with certified heritage experts and only 4% of local governments that have established cultural heritages. To date, there is none regency/municipal government that has organized cultural heritage registration for public. The purpose of this study is to find solution so that the central government can urge the regency/municipal governments to organize cultural heritage registration for public. This research used literature study to get data about the socialization that have been conducted previously. The literature study was also in form of theoretical review about public awareness campaigns principles and cultural heritage preservation. The result of this study is a recommendation for the central government to organize public awareness campaign about cultural conservation.Keywords: Cultural conservation, Public awareness campaign, Central government, Local governmentAbstrak.Undang-Undang Nomor 11 Tahun 2010 tentang Cagar Budaya mengamanatkan masyarakat untuk mendaftarkan benda, bangunan, struktur, situs atau kawasan mereka yang memiliki nilai penting bagi sejarah, ilmu pengetahuan, pendidikan, agama, dan/atau kebudayaan kepada pemerintah kabupaten/kota untuk ditetapkan atau tidak ditetapkan sebagai cagar budaya. Dalam rangka melaksanakan amanat tersebut, sejak tahun 2013 pemerintah telah menyosialisasikan pelestarian cagar budaya kepada 69% pemerintah daerah. Namun demikian, respon pemerintah kabupaten/kota untuk menyelenggarakan pendaftaran cagar budaya milik masyarakat masih relatif rendah. Hingga akhir tahun 2017, hanya terdapat 13.5% pemerintah daerah yang memiliki Tim Ahli Cagar Budaya bersertifikat dan 4% pemerintah daerah yang telah menetapkan cagar budaya. Hingga tulisan ini dibuat belum ada pemerintah kabupaten/kotayang menyelenggarakan pendaftaran koleksi/properti milik masyarakat untuk ditetapkan sebagai cagar budaya. Permasalahan kajian ini adalah bagaimana pemerintah pusat dapat mendorong pemerintah kabupaten/kota untuk menyelengarakan pendaftaran cagar budaya milik masyarakat. Kajian dalam artikel ini menggunakan kajian kepustakaan terhadap data sosialisasi pendaftaran cagar budaya yang pernah dilakukan oleh Pemerintah Pusat. Kajian kepustakaan juga berupa KALPATARU, Majalah Arkeologi Vol. 27 No. 1, Mei 2018 (15-30) 16 tinjauan teoretis mengenai prinsip-prinsip membangkitkan kesadaran masyarakat secara umum dan terhadap pelestarian cagar budaya secara khusus. Hasil kajian mengusulkan agar pemerintah Pusat menyelenggarakan Kampanye Pelestarian Cagar Budaya dengan menggunakan metode kampanye kesadaran masyarakat.Kata Kunci: Pelestarian Cagar Budaya, Kampanye Kesadaran Masyarakat, Pemerintah Pusat, dan Pemerintah Daerah